Mechanisms for Reviving the Intangible Cultural Heritage to Revitalize Urban Spaces - Eman Tahseen; Saad Khudair Al-Jumaily (International Journal of Environment, Engineering and Education, 2020)
The intangible cultural heritage is considered to be of value to the local community, as it contributes to the revitalization of urban spaces, its revitalization and making it vibrant with life, population, and society, as revitalizing the intangible aspects of culture means restoring the effectiveness of urban spaces through cultural performances and activities, and these activities are a source of attraction for society and in places, Different such as the street, squares, and urban parks, as this activation process leads to the revitalization of the economic aspects through an interest in providing shops for users and restaurants and places for rest with the social, cultural and physical aspects that are related to each other Some.